1999
DOI: 10.1111/j.1574-0862.1999.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Family farm dynamics in Canada and Israel: the case of farm exits

Abstract: Canada is one of the few countries for which data exist on individual family farms over time. Using these data, researchers have been able to show that much of the microdynamics of family farms in Canada (e.g. changes in size distribution) can be attributed to farmer entry and exit. However, the behavioral aspects of the exit decision received little attention in the literature. A comparison of Canadian and Israeli data could help us understand these behavioral aspects because of the vast institutional differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 11 publications
11
83
2
4
Order By: Relevance
“…In earlier studies, the probability of transferring the farm to a new entrant has been found first to increase with a farmer's age and then beyond a certain age limit to decrease (Kimhi and Bollman, 1999;Stiglbauer and Weiss, 2000;Kimhi and Nachlieli, 2001). This is especially the case in family successions.…”
Section: Variable Definitionsmentioning
confidence: 93%
See 2 more Smart Citations
“…In earlier studies, the probability of transferring the farm to a new entrant has been found first to increase with a farmer's age and then beyond a certain age limit to decrease (Kimhi and Bollman, 1999;Stiglbauer and Weiss, 2000;Kimhi and Nachlieli, 2001). This is especially the case in family successions.…”
Section: Variable Definitionsmentioning
confidence: 93%
“…Previous studies on farmers' exit decisions have used, multinomial logit (e.g. Stiglbauer and Weiss, 2000), probit (Kimhi and Bollman, 1999;Kimhi and Nachlieli, 2001) or bivariate probit models (Glauben et al, 2004). Earlier studies on spousal retirement behaviour and retirement decisions, on the other hand, have used among others competing risk duration models (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…studies on farm exit (e.g. Kimhi and Bollman, 1999;Weiss, 1999;Dries and Swinnen, 2004;Glauben et al, 2004). Moreover, these studies do not use the analytical framework of tipping points and resilience.…”
Section: Introductionmentioning
confidence: 99%
“…A probit model was constructed to estimate the exit probability and to seek the determinants of exit behavior. The main finding of Kimhi and Bollman's (1999) study was that the dependency of exit behavior on farm size differs between the two countries mainly due to institutional differences. The authors also found that the exit probability decreased with the extent of off-farm work in both Israel and Canada.…”
Section: Introductionmentioning
confidence: 99%